2020
DOI: 10.1177/1947603520931170
|View full text |Cite
|
Sign up to set email alerts
|

PRP Injections for the Treatment of Knee Osteoarthritis: A Meta-Analysis of Randomized Controlled Trials

Abstract: Objective To evaluate effectiveness, in terms of patient-reported outcome measures, of platelet-rich plasma (PRP) injections for knee osteoarthritis compared to placebo and other intraarticular treatments. Design PubMed, Cochrane Library, Scopus, Embase, Web of Science, as well as the gray literature were searched on January 17, 2020. Randomized controlled trials (RCTs) comparing PRP injections with placebo or other injectable treatments, in any language, on humans, were included. Risk of bias was assessed fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
124
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 176 publications
(133 citation statements)
references
References 79 publications
8
124
0
1
Order By: Relevance
“…PRP has shown a very good promise as an agent of tissue repair and regeneration. Most of the studies involving the use of PRP point towards some improvement in pain and function but lack proper documentation and analysis [12][13][14][15]. Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…PRP has shown a very good promise as an agent of tissue repair and regeneration. Most of the studies involving the use of PRP point towards some improvement in pain and function but lack proper documentation and analysis [12][13][14][15]. Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of PRP for symptomatic tendinopathy is controversial, with mixed results reported. Animal studies generally show histologic improvement following PRP infiltration for tendinopathy (181). These studies showed that mechanical loading is regenerative to tendons, and the load is synergistic with PRP injections for tendon healing.…”
Section: Combining Prp With Rehabilitationmentioning
confidence: 93%
“…PRP treatment involves injecting concentrated platelets in the local tissue milieu to modulate pain and foster tissue repair [ 197 , 198 ]. The strongest clinical evidence exists in knee OA.…”
Section: Combining Platelet-rich Plasma Applications With Rehabilmentioning
confidence: 99%